ANA HONCU, AEDES AD DANUVIUM. INIȚIATIVE PUBLICE ŞI PRIVATE ÎN FENOMENUL EDILITAR DIN PROVINCIILE DACIA ŞI MOESIA INFERIOR (SECOLELE I-III P. CHR.), (AEDES AD DANUVIUM. PUBLIC AND PRIVATE BUILDING INITIATIVES IN THE PROVINCES OF DACIA AND MOESIA INFERIOR, 1ˢᵀ - 3ᴿᴰ C. AD), IAŞI: EDITURA UNIVERSITĂȚII "ALEXANDRU IOAN CUZA", 2022. - SOCACIU, Sergiu (Studia Universitatis Babeș-Bolyai Historia, 2023)
The question of Romanization and the degree to which it took place within the Roman frontier provinces has attracted the interest of several researchers over time. One of the great challenges of such a research direction is the identification of the diffusion level of the Roman culture and values within the newly annexed provinces. The researcher's effort is channeled towards identifying the cultural and social aspects that could indicate the degree to which the population of a certain province has appropriated the Roman lifestyle, adopting, at the same time, that forma mentis characteristic of Roman culture and civilization. There are several means by which such aspects can be identified in the provincial world. Among these, the most suggestive ones can be inferred from the study of the urban planning initiatives carried out within the various settlements in the provinces, and of the phenomenon of euergetism, which is the basis of such initiatives. Within the Lower Danube provinces, several studies were carried out regarding the urban planning initiatives and the aspects of urbanism in these provinces. The most recent work that addresses the issue of these phenomena belongs to the researcher Ana Honcu and we will present it below.